Determinants of winter browsing intensity on young Scots pine (Pinus sylvestris) by moose (Alces alces) across a bio-geographical gradient in Sweden - Vysinova, Lenka (2010)
Intensive moose (Alces alces) browsing pressure has a large impact on ecosystems as well as economics of forestry companies. Moose winter browsing pressure on young Scots pine (Pinus sylvestris) is affected by a range of factors and I modelled effects of such factors across a bio-geographical gradient in Sweden. The tested factors were: density of moose, roe deer (Capreolus capreolus), red deer (Cervus elaphus), and fallow deer (Dama dama), forage availability, height of surveyed tree, thinning, pre-commercial thinning, clear-cutting, dominating forest, tree density, habitat productivity, number of days with snow cover, distance to road, and distance to settlements. The analyses were carried out at three spatial scales – plot, tract, and landscape scale. The data was extracted from a field survey and a digitalized forest stand database of a forestry company. At the plot scale, in the minimal adequate model, explaining browsing pressure on pine, the factors study area, moose density, dominating forest type and height of surveyed pines were significant. At the tract scale, the factors study area, moose density and dominating forest were significant. At the landscape scale, the proportion of pine in the forest was negatively related to browsing. Nosignificant relationships between browsing pressure and the other factors were found. These finding suggest that dominating type of the forest is the most general factor affecting browsing pressure at all spatial scales. The browsing pressure was nearly significantly higher in the mixed coniferous forest than in the other types of the forest at the tract spatial scale. The moose density is significant at smaller scales, in contrast to the largest scale. This result supports the idea that the browsing pressure at larger scales is affected by other factors than moose density.